Factor influencing purchase decision on smartphone among Generation-Y in Pasir Gudang / Nur Amirah Rozman - Rozman, Nur Amirah (Faculty of Business and Management, 2019)
The study is intending to investigate the factor influencing purchase decision on smartphone among generation-y in Pasir Gudang. This study consist four independent variables which is brand concern, convenience, price and social influence. While dependent variables is generation-y purchase decision on smartphones. Total of questionnaires was keyed-in and analyzed by using SPSS software version 25. Furthermore, this research has used non-probability methods which is convenience sampling. Convenience sampling are used to obtain accurate date from the targeted respondents. All data were collected for the purpose to create analysis of descriptive, correlation and also regression analysis. In this study, finding shows that there were three independent variables that has significant relationship towards the purchase decision on smartphone among generation-y which are brand concern, convenience and also the social influence. From this, we can see that the finding is useful for the smartphone producer so they can produce a better smartphones based on this study.